Compliance Level of the Wear of Masks of Street Vendors During the Covid-19 Pandemic - PH, Livana; Irianto, Sugeng Eko; Kurian, Midhu; Gouda, Amel Dawod Kamel (Journal of Economics and Public Health, 2022)
The number of confirmed cases of Covid-19 is increasing. Prevention efforts are carried out by wearing personal protective equipment, one of which is wearing a mask. The study aims to identify the wear of masks of street vendors as an effort to prevent COVID-19. This study involved 90 street vendors selling in the District X area in Indonesia. The results showed that the majority of street vendors were taught to wear masks.